Improving critical thinking skills of high school students through guided inquiry implementation for learning reaction rate concept in chemistry - Mila Meita Sari; Muchlis Muchlis (Jurnal Pijar Mipa, 2022)
This research was conducted to know (1) the implementation of the guided inquiry learning model; (2) student activities; (3) critical thinking skills; and (4) student responses. The type of research was used pre-experimental with one group pretest-posttest design. The population in this research was all students of class XI MIPA SMAN 1 Gedangan Sidoarjo in the 2021/2022 academic year, with 11th grade MIPA 6 as the sample. The research results show that the learning model is implemented in the very good category with the percentage of implementation at first is 96.09% and the second meetings are 98.83%. The activity of students is very good and supports the effectiveness of the learning model, with the percentage at the first and second meetings being 97.9% and 98.7%, respectively. (3) There was an increase in critical thinking skills from acquiring the N-Gain score, 87.10% of students in the high category and 12.90% of students in the medium category, and the classical student learning outcomes are 87.10%. (4) Student response to the learning model that has been applied is very good, with a percentage of 90.37%. Based on this, it indicated that the guided inquiry model could improve the critical thinking skills of 11th grade students on the reaction rate material.